O clima de Teófilo Otoni (MG): integração escalar, tipos de tempo e impactos ambientais - Fabricio Lisboa Vieira Machado (2016)
Scientific research in climatology that do not rely primarily on climatic classification of valuation models and synoptic or regional aspects are scarce, especially when far from large urban centers. One example is the region of the valley of the Mucuri, in northeastern Minas Gerais, which has not experienced productions that addressed the rhythmic climate analysis or the identification of environmental impacts. In general, this study aimed to evaluate the interrelationship between factors and elements responsible for producing the climates where the city of Teófilo Otoni (MG) is, with a view to proposing the synthesis in climate units and support municipal planning. Therefore, the scale and systemic decomposition is favored, necessary to geographical climate study, which was defined methodological script adapted to assess the upper and lower ranges. From the interpretation of the data of the regional official historical data and measurements in the field with the built meteorological minishelters (conducted in different landscape contexts and altimetry levels), was evaluated the spatial differential impact of energy balance components, where the average temperature daily air measured in the city center proved to 5.6°C higher than the rural and forest areas. Under action of the South Atlantic Subtropical Anticyclone (atmospheric higher frequency system), hourly humidity contrast between urban and natural areas, in some situations, it was more than 20%, due to the reduction of the moisture available balance in the atmosphere on city (less evapotranspiration). Under acting unstable summer systems, recurrent historical problem was identified in the city and region, associated with the rainfall impact on land use. Finally, the effort carried out synthesis of research on climate units, which identified two natural mesoclimates controlled mainly by the relief factor, plus four natural and urban topoclimates, reflecting potential and limitations uses of space.